PENGARUH MELAMIN DALAM PEREKAT UREA FORMALOEH IDA TERHADAP BEBERAPA SIFAT KAYU LAPIS MERANTI The (lffect of melamine composition in urea formaldehyde resin glue on the properties of merenti plywood - Rodjak Memed (Jurnal Penelitian Hasil Hutan, 1990)
The "fiy1iialal'ld :chemical properties of  urea formaldehyde resin were tested  based on the Indonesian Standard. which cO'nlittfl)t appearatlceipropertie1, pH, tree fOrmaldehyde, solid content and pot'~llfe. TM   re.ult 1hou>s that most of the prripertiu    co11form,fbith.  the  nanclard :                                                                                                                                      .                                                        .                                             'n.w:addinon.  1 scent '.melamine  qnd ao ~rcent   extender 1'r:Oduces plywood  with formAlile1&yde emwionmeetini the J 981. American 1tanclqrd.  The effect of melamine addition toat not signi(tt:ant.The effect of extender on theother htind 1uu•iiwhJ1.  1igni'(ieant'effect  on the ilecr:ea_1e of formaldehyde emiaion tn  plywood.          Allplytt;ooli bonittir; 1tren,.th meet the Indonesian, Japaneseand German standard. The effect of melamine addition of lO dd  16 enton      thplywood   bonding atrength' was not significant.